Escala de avaliação do autocuidado de pacientes com insuficiência cardíaca : validação clínica - Oliveira, Sherida Karanini Paz de (2015)
Self - care should be performed by patients with heart failure (HF) to prevent complications and health promotion. The objective was to validate the Rating Scale of Self Care of Patients with Heart Failure (RSSCPHF ). Methodological study, developed in three stages, which followed as a reference of the Psychometric Pasquali model. In the first stage was carried out a pre - test with application of the second version of EAAPIC in two private hospitals with cardiology ca re in Fortaleza - CE, which provided discussion group with five technical judges. In the second stage, was realized the empirical polo with the application of the third version of RSSCPHF to 276 patients, in addition to sociodemographic, clinical and laborat ory data, from an outpatient clinic of a tertiary hospital in Fortaleza - CE . And at the third stage was held the analytical procedure through the construct validity assessed by factor analysis and by reliability, wich the internal consistency was assessed u sing Cronbach's alpha and stability measured by test - retest and intraclass correlation coefficient. This study was approved by the Ethics and Research Committee of the institution under n ° 499 793. As a result, in the first stage, after the pre - test, modi fications were undertaken in RSSCPHF looking for a more clear and understandable instrument which resulted in the third version of the scale. In the second stage, showed a predominance of males (60.1%), aged 40 - 59 years (54.8%), low education (45.6%) and income (54.7%), absence of labor activity (78.2%), married or in stable relationships (68.1%), non - white (75%), Catholics (64.5%), more than 5 years of diagnosis, ischemic etiology, functional class II, lipid profile appropriate, ejection fraction of the l eft ventricle below 55%, overweight and stable vital signs. As the exploratory factor analysis, the third stage, the RSSCPHF has four domains and 12 items and explains 51.309% of the self - care of patients with HF practice. We conducted confirmatory fac tor analysis which confirmed the initial factor model and the quality of the model fit. The Cronbach's alpha was 0.568, indicating low homogeneity. As for stability, the intraclass correlation coefficients of the items can be considered moderate to high (R = 0 .583 to 1.000) for most items. The reliability of the instrument was 0.810, confirming that the RSSCPHF reliable with regard to stability. It was also found that patients practicing self - care actions (81.8%), with deficits in knowledge items and adaptation , recognition and demand for health services in the presence of symptoms of HF decompensation and vaccination. Found a significant association between self - care and gender (p = 0.015), age (p = 0.044), income (p = 0.000), educational level (p = 0.001), fun ctional class ( p = 0.041), fatigue (p = 0.002) , paroxysmal nocturnal dyspnea (p = 11 0.000), orthopnea (p = 0.036), LDL levels (p = 0.018) and respiratory rate (p = 0.000). It follows that the EAAPIC is a valid and reliable measure instrument in terms of sta bility, able to assess the self - care of patients with heart failure and identify their needs. However, we suggest further studies to review the internal consistency of the instrument.